Neuropilin-2 expression affects the increased vascularization and is a prognostic factor in osteosarcoma. - Handa, A; Tokunaga, T; Tsuchida, T; Lee, Y; Kijima, H; Yamazaki, H; Ueyama, Y; Fukuda, H; Nakamura, M (2000)
Osteosarcoma is a malignant bone tumor characterized by hypervascularity. Neuropilins (NRPs), which is expressed by human tumor cells, is known to be a potent receptor for vascular endothelial growth factor (VEGF). We examined NRPs mRNA expression in 30 osteosarcomas. The osteosarcomas with NRP2 expression (n=24) showed a significantly increased vascularity (P<0.0014, Mann-Whitney U test). Osteosarcomas with NRP2 showed significantly poorer prognosis than those without NRP2 (P=0.016, Wilcoxon's test). These results suggest that NRP acts as a VEGF-amplifier in a paracrine or autocrine manner in the osteosarcoma. NRP2 expression cooperatively promotes angiogenesis and growth in osteosarcomas with VEGF expression.